2005
DOI: 10.1016/j.icesjms.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Possible ecosystem impacts of applying MSY policies from single-species assessment

Abstract: Ecosim models have been fitted to time-series data for a wide variety of ecosystems for which there are long-term data that confirm the models' ability to reproduce past responses of many species to harvesting. We subject these model ecosystems to a variety of harvest policies, including options based on harvesting each species at its maximum sustainable yield (MSY) fishing rate. We show that widespread application of single-species MSY policies would in general cause severe deterioration in ecosystem structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(198 citation statements)
references
References 17 publications
5
190
2
1
Order By: Relevance
“…However, in the case of our HollingTanner prey-predator system, fishing of the prey species at the MSY level may be a sustainable fishing policy. Also, Walters et al [2] showed that the widespread application of single species MSY policies would in general cause severe deterioration in the ecosystem structure, in particular the loss of top predator species. However, we observe that the predator species can survive even if the fishing reaches the MSY level on the prey species and hence we found an exception to the rule that Walters et al [2] stated.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of our HollingTanner prey-predator system, fishing of the prey species at the MSY level may be a sustainable fishing policy. Also, Walters et al [2] showed that the widespread application of single species MSY policies would in general cause severe deterioration in the ecosystem structure, in particular the loss of top predator species. However, we observe that the predator species can survive even if the fishing reaches the MSY level on the prey species and hence we found an exception to the rule that Walters et al [2] stated.…”
Section: Resultsmentioning
confidence: 99%
“…The Congressional mandates, as interpreted by environmental organizations, courts, and government lawyers, make it difficult for stock assessments to address spatial and temporal heterogeneity, such as variables relating to benthic habitat, oceanographic conditions, trophic relations, fishing gear usage, or species cycles of migration, growth, and reproduction. Assessment scientists generally assume that their datasets have sufficient spatial and temporal coverage to incorporate these variables, despite extensive evidence to the contrary (Ludwig et al 1993;Wilson et al 1999;Jackson et al 2001;Ames 2004;Walters et al 2005). More concerning, "limited access" and "catch share" policies promoted increasingly by federal managers since the 1980s, and intended to maintain maximum sustainable yield, discourage fishermen from adapting to dynamic marine systems by shifting fishing effort among a number of target species (Wilson et al 1991;Brewer 2011).…”
Section: Fishing Practices and Policiesmentioning
confidence: 99%
“…Local stock depletions are not detected until the estimate of total biomass falls outside the confidence limits for the entire stock assessment. This limitation is inherent in the assessment procedure and explains why local depletions have repeatedly been able to cascade into widespread stock collapses (Walters et al 2004).…”
Section: Constraints On Recoverymentioning
confidence: 99%